Association Between IL-28B Polymorphism and Clinical Laboratory Features in Patients with Chronic Hepatitis D - Bayarsaikhan, Uyanga; Gidaagaya, Sarantuya; Namdag, Bira; Batjargal, Azjargal (Central Asian Journal of Medical Sciences, 2017)
Objectives: We aimed to determine an association between IL-28B rs12989760 single nucleotide polymorphism (SNP) and clinical laboratory parameters in patients with chronic hepatitis D. Methods: A total of 59 patients who were chronically infected with HDV were had their serum tested for the presence of qHBsAg, anti-HBs, HBeAg, anti-HBe, anti-HBc, anti-HCV, anti-HDV IgM, anti-HDV IgG, HDV RNA, HBV DNA and AFP. Liver function tests, coagulation tests and CBC were also performed. IL-28B polymorphism was performed using a TaqMan 5' allelic discrimination assay by real time PCR. Results: Of these 59 patients, 40 patients (67.8 %) carried the rs12979860CC homozygote genotype, 11 patients (18.6%) were rs12979860CC homozygote and 8 patients (13.6%) were rs12979860CT heterozygote. Alkaline phosphatase and direct bilirubin values were higher (p<0.05) and total protein levels were lower (p<0.05) in patients who were homozygotes for the T allele as opposed to the carriers of the C allele. AFP levels were significantly higher (p=0.02) in the rs12979860 TT genotype group. Liver enzymes including AST, ALT and GGT were significantly not higher in patients who carry C allele (p>.05). Conclusion: The most frequent genotype was IL-28B rs12979860CC among patients with chronic hepatitis D. The IL-28B rs12979860 polymorphism was associated with some abnormal liver function test parameters and AFP levels. Additional studies are necessary to understand the immune mechanisms of IL-28B polymorphism in HDV infection.